Bedrock geology of DFDP-2B, central Alpine Fault, New Zealand. Issue 4 (2nd October 2017) - Toy, Virginia Gail; Sutherland, Rupert; Townend, John; Allen, Michael J.; Becroft, Leeza; Boles, Austin; Boulton, Carolyn; Carpenter, Brett; Cooper, Alan; Cox, Simon C.; Daube, Christopher; Faulkner, Daniel R.; et al.
ABSTRACT: During the second phase of the Alpine Fault, Deep Fault Drilling Project (DFDP) in the Whataroa River, South Westland, New Zealand, bedrock was encountered in the DFDP-2B borehole from 238.5–893.2 m Measured Depth (MD). Continuous sampling and meso- to microscale characterisation of whole rock cuttings established that, in sequence, the borehole sampled amphibolite facies, Torlesse Composite Terrane-derived schists, protomylonites and mylonites, terminating 200–400 m above an Alpine Fault Principal Slip Zone (PSZ) with a maximum dip of 62°. The most diagnostic structural features of increasing PSZ proximity were the occurrence of shear bands and reduction in mean quartz grain sizes. A change in composition to greater mica:quartz + feldspar, most markedly below c. 700 m MD, is inferred to result from either heterogeneous sampling or a change in lithology related to alteration. Major oxide variations suggest the fault-proximal Alpine Fault alteration zone, as previously defined in DFDP-1 core, was not sampled.